Genetic Structure and Diversity of Rice Root Nematode (Hirschmanniella mucronata) in Thailand - Siwakorn Supajariyapong; Hans Jørgen Lyngs Jørgensen; Pornthip Ruanpanun (Agronomy)
Rice root nematodes (Hirschmanniella spp.) cause serious damage to rice in various rice-producing countries in Asia. Nonetheless, there is limited information about the genetic diversity and structure of these nematodes, including in Thailand, where the current study explored the diversity and structure of Hirschmanniella spp. from 57 paddy fields in major rice-growing areas across the country. Using morphological characteristics and internal transcribed spacer rDNA sequencing, we identified all samples as Hirschmanniella mucronata. The use of the Inter-Simple-Sequence-Repeats-based delta K statistical test and principal coordinate analysis revealed two different genetic groups from three distinct geographical regions including the north and the northeast (Group 1) and the central (Group 2) regions. While the unbiased expected heterozygosity indicated low genetic diversity of H. mucronata in Thailand (0.149), the Shannon information index indicated there was higher diversity in Group 2 (0.259) than Group 1 (0.228). The AMOVA confirmed high genetic variation within such groups (76%), but low genetic variation between the two groups (24%). There was no clear correlation between genetic diversity and geographic distance. Given the presence of H. mucronata in almost all rice-growing countries, this first study of H. mucronata populations has provided fundamental knowledge that should help to combat this pest in the rice production system.